The Coordinated Role of CYP450 Enzymes and P-gp in Determining Cancer Resistance to Chemotherapy - Azzariti, Amalia; Porcelli, Letizia; Elisa Quatrale, Anna; Silvestris, Nicola; Paradiso, Angelo (Current Drug Metabolism, 2011)
The relationship between CYP450 and P-gp occurs at different levels. It is known that certain substrates of P-gp undergo metabolic transformations by various CYP450 isoforms; in addition some of them demonstrated to be activators of both P-gp and CYP450. The majority of such compounds are well-known chemotherapeutics, therefore the purpose of this review is to clarify whether there is a relationship between the simultaneous modulation of CYP450 and P-gp and the onset of drug resistance in tumors treatment. Here, we discuss the biological aspects of the topic in relation to the various tissues distribution of CYP450 and P-gp, the recent findings regarding the ability of some chemotherapeutics in modulating both P-gp and CYP450, whether this modulation is ultimately responsible for the onset of drug resistance in cancer treatment and the promising role of gene polymorphisms in determining the interindividual variability in drug responses in clinical practice.
Keywords: Cancer